Beautiful : [large type] a novel - Steel, Danielle (Random House Large Print, 2022)
Veronique Vincent graces the covers of magazines and walks the runways of haute couture shows across the globe, yet she prefers spending time at home or with her boyfriend. An explosion at Zaventem Airport in Brussels changes her life forever: Veronique finds herself hospitalized and alone after the blast kills both of the people she loved most. Severely injured, she plunges into seclusion and struggles to discover what truly matters in life. When her mother's will reveals long-held secrets, Veronique begins to find peace in helping others, and redefining what it truly means to be beautiful. -- adapted from back cover.